Seizure-associated hippocampal volume loss: A longitudinal magnetic resonance study of temporal lobe epilepsy - Briellmann, Regula S.; Berkovic, Samuel F.; Syngeniotis, Ari; King, Mark A.; Jackson, Graeme D. (Annals of neurology, 2002)
This longitudinal quantitative magnetic resonance imaging study of 24 patients with mild temporal lobe epilepsy shows an ipsilateral hippocampal volume decrease of 9% (range, −30 to +0.5%; p = 0.002, paired t test) over a period of 3.5 ± 0.7 years. The hippocampal volume loss was correlated to the number of generalized seizures between the scans (p = 0.0007, r = 0.6), suggesting seizure‐associated hippocampal damage.